Screening and Characterizing Tyrosinase Inhibitors from Salvia miltiorrhiza and Carthamus tinctorius by Spectrum-Effect Relationship Analysis and Molecular Docking. (9th May 2018) - Wang, Ya-Li; Hu, Guang; Zhang, Qian; Yang, Yu-Xiu; Li, Qiao-Qiao; Hu, Yuan-Jia; Chen, Hua; Yang, Feng-Qing
Abstract : Tyrosinase (TYR) is a rate-limiting enzyme in the synthesis of melanin, while direct TYR inhibitors are a class of important clinical antimelanoma drugs. This study established a spectrum-effect relationship analysis method and high-performance liquid chromatography-mass spectrometry (LC-MS) analysis method to screen and identify the active ingredients that inhibited TYR in Salvia miltiorrhiza – Carthamus tinctorius (Danshen–Honghua, DH) herbal pair. Seventeen potential active compounds (peaks) in the extract of DH herbal pair were predicted, and thirteen of them were tentatively identified by LC-MS analysis. Furthermore, TYR inhibitory activities of five pure compounds obtained from the DH herbal pair were validated in the test in which kojic acid served as a positive control drug. Among them, three compounds including protocatechuic aldehyde, hydroxysafflor yellow A, and tanshinone IIA were verified to have high TYR inhibitory activity (IC50 value of 455, 498, and 1214 μ M, resp.) and bind to the same amino acid residues in TYR catalytic pocket according to the results of the molecular docking test. However, the other two compounds lithospermic acid and salvianolic acid A had a weak effect on TYR, as they do not combine with the active amino acid residues or act on the active center of TYR. Therefore, the developed methods (spectrum-effect relationship analysis and molecular docking) could be used to effectively screen TYR inhibitors in complex mixtures such as natural products.